(untitled) (Global Journals of Research in Engineering, 2022)
This project will be of great impact for the population of the Azuero region for the Technological University of Panama UTP and for the inhabitants of Macaraquita Chepo and Las Minas since this center will be the appropriate setting where lectures and courses will be held on the practical application of technological trends in sustainable production focused on the dissemination of our research so that the following projects will be located in interconnected facilities with towers and wires for moving Training center section Section of orchid bioparks Wind generation section Section of water processing plant Aquaculture section Greenhouse section of healthy fruits and apiary In these sections theoretical-practical training will be conducted for the population on each of the aforementioned projects this will provide the institution with better communication with the community and thus be able to continue with the post-construction work which would be the maintenance work care and development of infrastructure and projects